Variational methods in the mechanics of solids : proceedings of the IUTAM Symposium on Variational Methods in the Mechanics of Solids held at Northwestern University, Evanston, Illinois, U.S.A., 11-13 September 1978 - Nemat-Nasser, S. (Pergamon Press, 1980)
Variational Methods in the Mechanics of Solids contains the proceedings of the International Union of Theoretical and Applied Mechanics Symposium on Variational Methods in the Mechanics of Solids, held at Northwestern University in Evanston, Illinois, on September 11-13, 1978. The papers focus on advances in the application of variational methods to a variety of mathematically and technically significant problems in solid mechanics. The discussions are organized around three themes: thermomechanical behavior of composites, elastic and inelastic boundary value problems, and elastic and inelasti.